Enhance The Brand Image Through Television Commercial (Tvc): A Case Study “Create Your Chance” of Tokopedia.Com and Apologizes of Bukalapak.Com - Ulani Yunus (Humaniora, 2016)
The purpose of this research was to describe how the brand image could be improved through television commercial (TVC) with a special theme. The focus of this research was how to improve the brand image through TVC with a special theme. This study was broken down into research questions (1) How does “Create Your Chance” TVC of Tokopedia.com increase brand awareness? (2) How does “Apologizes” TVC increase Bukalapak.com, (3) How does brand image as if formed by Tokopedia.com and Bukalapak.com. The concept used was the elements of the brand image and mass communication. The paradigm of descriptive qualitative methods was to be a way of expressing the data in this study that supported by two previous quantitative research. The results show that (1) "Create Your Chance" TVC of Tokopedia.com increases brand awareness through visualization and the words that exist in the TVC as being able to see the opportunities, such as visualization of barber who also received job through online booking, (2) "Apologize" TVC improves brand image of Bukalapak.com as online sites that provides competitive pricing and managed directly by the young CEO who humble so deliberately apologize for the lack of focus of the employees of the many offices as a buyers, (3) Brand image is enhanced by tokopedia.com and Bukalapak.com with touch the dimension of emotional of audience.